Transforming the empowerment of rural poor and vulnerable farmers through collaborative governance - Dedy Suhendi; M. Amin (Lentera Negeri, 2026)
This study explores the transformation of the empowerment of poor and vulnerable farmers through a collaborative governance approach in East Lombok Regency, West Nusa Tenggara. Farmer poverty in this region is driven not only by low income but also by structural constraints, including limited access to land, capital, technology, market information, weak farmer institutions, ecological pressures, and commodity price fluctuations. The study examined how collaborative governance strengthens farmers’ socio-economic resilience and identified the factors facilitating and constraining its implementation. A descriptive qualitative design using purposive sampling involved 25 informants comprising poor farmers, farmer group leaders, agricultural extension officers, village officials, and community leaders. Data were collected from February to June 2024 through interviews, participant observation, and the analysis of regional regulations, official statistics, and institutional reports. Data were analyzed using Braun and Clarke’s six-phase thematic analysis, while credibility was enhanced through source and method triangulation and member checking. The findings indicate that participants reported improved farming practices, livelihood diversification, market access, and stronger farmer organizations across rice, tobacco, horticultural, and garlic farming systems. However, persistent challenges included unequal stakeholder participation, fragmented cross-sectoral coordination, limited institutional capacity, and unequal partnership arrangements. These findings suggest that collaborative governance supports farmer empowerment, although its effectiveness depends on inclusive participation, adaptive coordination, and context-sensitive implementation rather than representing a direct causal determinant of improved welfare.